Exploring the issue of asymmetry in analysing educational poverty using Qualitative Comparative Analysis (QCA) - Judith Glaesser (Methodological Innovations, 2021)
This article discusses the issue of conceptual asymmetry and associated analytical challenges, with the concept of educational poverty serving as an empirical example. The notion of educational poverty has been introduced by Allmendinger to describe, analogously to material poverty, a severe shortage or complete lack of educational qualifications. Poverty may be considered to be the opposite of wealth, but absence of poverty is not so obviously the same thing as wealth – in fact, it almost certainly is not. Neither is absence of wealth the same thing as poverty. However, both poverty and wealth are measured using the same raw measure, monetary resources in the case of material poverty or wealth and educational certificates in the case of educational poverty or wealth. This asymmetry and related issues lead to interesting conceptual and methodological challenges in analysing factors contributing to the twin outcomes of educational poverty and wealth, as well as the absence of each. These conceptual or methodological challenges are the focus of this article. Given that both poverty and wealth are experienced by only a minority of individuals, the article also addresses the question of whether explaining relatively rare events requires a different approach than explaining more commonly occurring events or outcomes. The analysis of asymmetry requires the use of a method which is able to distinguish between the presence of an outcome and its absence. This capability is one of the features of Qualitative Comparative Analysis, making it an eminently suitable method for this issue. The empirical example draws on the German National Educational Panel Study. The analyses focus on the four outcomes of educational poverty and its absence and educational wealth and its absence, demonstrating that different pathways are associated with each.